Mitral Annular Forces and Their Potential Impact on Annuloplasty Ring Selection - Jedrzejczyk, Johannes H.; Carlson Hanse, Lisa; Javadian, Shadi; Skov, Søren N.; Hasenkam, J. Michael; Thørnild, Marcell J. (Frontiers in Cardiovascular Medicine, 2022)
Objectives: To provide an overview that describes the characteristics of a mitral annuloplasty device when treating patients with a specific type of mitral regurgitation according to Carpentier's classification of mitral regurgitation. Methods: Starting with the key search term "mitral valve annuloplasty", a literature search was performed utilising PubMed, Google Scholar, and Web of Science to identify relevant studies. A systematic approach was used to assess all publications. Results: Mitral annuloplasty rings are traditionally categorised by their mechanical compliance in rigid-, semi-rigid-, and flexible rings. There is a direct correlation between remodelling capabilities and rigidity. Thus, a rigid annuloplasty ring will have the highest remodelling capability, while a flexible ring will have the lowest. Rigid- and semi-rigid rings can furthermore be divided into flat and saddled-shaped rings. Saddle-shaped rings are generally preferred over flat rings since they decrease annular and leaflet stress accumulation and provide superior leaflet coaptation. Finally, mitral annuloplasty rings can either be complete or partial. Conclusions: A downsized rigid- or semi-rigid ring is advantageous when higher remodelling capabilities are required to correct dilation of the mitral annulus, as seen in type I, type IIIa, and type IIIb mitral regurgitation. In type II mitral regurgitation, a normosized flexible ring might be sufficient and allow for a more physiological repair since there is no annular dilatation, which diminishes the need for remodelling capabilities. However, mitral annuloplasty ring selection should always be based on the specific morphology in each patient.